OG’ZAKI VA YOZMA NUTQDA TILNING TASVIRIY IFODALARI (INGLIZ VA O’ZBEK TILLARI MISOLIDA) - Najmiddinova Durdona, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This abstract explores the importance of phraseological units in linguistics and their contribution to the richness of a language. Phraseology plays a crucial role in highlighting the unique characteristics of each language and reflects the culture, traditions, and history of the people. It discusses how periphrasis and figurative expressions enhance the expressiveness and appeal of speech, analyzing their meanings and usage depending on context. The article also compares and contrasts figurative expressions in English and Uzbek.